(untitled) (Research, Society and Development, 2024)
Introduction: Endocrine Disruptors (EDs) are chemicals that are easily accessible to humans and present in everyday life. Therefore, these chemicals such as phthalates, bisphenol A (BPA), bisphenol S (BPS), among others, are associated with some diseases such as diabetes and conditions of the female reproductive system, such as endometriosis and Polycystic Ovary Syndrome (PCOS). Objective: To evaluate the potential influences that endocrine disruptors have on female health. Methodology: This is a narrative review based on the analysis of review articles and scientific studies published between 2014 and 2024, with the databases used being PubMed, Scielo and EBSCO, so that the criteria for inclusion of articles was based on content analysis, title analysis and consequent relevance to the theme; the health descriptors used were Polycystic Ovarian Syndrome (PCOS), endocrine disruptors, type 2 diabetes. Results: The selected articles analyzed demonstrate data indicating a possible relationship between contact with EDs and the incidence of diabetes, PCOS, endometriosis, cancer and infertility. Conclusion: This study elucidated a significant association between exposure to EDs and diseases prevalent in society, especially among women, such as PCOS, endometriosis, diabetes, obesity and cancer.